Riding the waves of power: Power fluctuation, cognitive energy, and goal pursuit - KIM, Hae-Lueng Rose (Institutional Knowledge at Singapore Management University, 2025)
A central finding in the power literature is that experiencing elevated power facilitates employees’ goal-relevant cognitions and behaviors. In this work, we suggest that the relationship between power and goal pursuit is more complex than previously assumed. Specifically, we examine how experiencing power fluctuation—alternating states of high and low power during the workday—can uniquely promote employees’ goal-relevant behaviors beyond the effect of static power. Integrating insights from the Dynamic Equilibrium Model of Organizing (DEMO) and the Model of Proactive Motivation (MPM), our work demonstrates that power fluctuation can facilitate employees’ cognitive energy, in a way that enhances their goal-relevant cognitions and behaviors (goal clarity, resource acquisition, personal initiative, and goal progress). Furthermore, our work considers for whom these benefits are most pronounced, showing that power fluctuation is more strongly associated with cognitive energy (and subsequent goal-relevant outcomes) for employees higher (vs. lower) in trait mindfulness. Taken together, our findings offer new insights and challenge traditional static conceptions of power by illustrating how daily fluctuations in power can serve as a motivational force that enhances goal pursuit in the workplace.